2013
DOI: 10.1182/blood-2013-05-503177
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin-modulated umbilical cord blood hematopoietic stem cell transplantation

Abstract: • Molecular profiling was used to optimize an ex vivo modulation protocol with dmPGE 2 for UCB transplantation.• Pulse treatment of UCB with dmPGE 2 is safe and may lead to accelerated UCB engraftment and preferential cord chimerism.Umbilical cord blood (UCB) is a valuable source of hematopoietic stem cells (HSCs) for use in allogeneic transplantation. Key advantages of UCB are rapid availability and less stringent requirements for HLA matching. However, UCB contains an inherently limited HSC count, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
266
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 287 publications
(273 citation statements)
references
References 34 publications
5
266
1
1
Order By: Relevance
“…[35][36][37] Additional strategies to increase homing and migration of cord blood cells are also under development using prostaglandin E2, CD 26/dipeptidyl peptidase (DPP-IV) and Fucosylation. [38][39][40] All of these approaches are in early clinical trials and are showing promising results. 41 Strategies to support immune reconstitution are more challenging but the emergence of new antivirals (Chimerix CMX001) and third-party cytotoxic T lymphocytes appear to have benefit in pilot clinical trials.…”
Section: Ucbt In Pediatricsmentioning
confidence: 99%
“…[35][36][37] Additional strategies to increase homing and migration of cord blood cells are also under development using prostaglandin E2, CD 26/dipeptidyl peptidase (DPP-IV) and Fucosylation. [38][39][40] All of these approaches are in early clinical trials and are showing promising results. 41 Strategies to support immune reconstitution are more challenging but the emergence of new antivirals (Chimerix CMX001) and third-party cytotoxic T lymphocytes appear to have benefit in pilot clinical trials.…”
Section: Ucbt In Pediatricsmentioning
confidence: 99%
“…45,46 Long-term engraftment occurred from the manipulated unit in 10 of 12 cases, but numbers of patients treated are too small to draw strong conclusions from this observation. 44 GvHD Grade II-IV and III-IV aGvHD occur in~30-50% and 10-20% of UCBT recipients, respectively. 7,[10][11][12][13]26,28,47,48 Despite the lower incidence of aGvHD relative to adult donor transplants and the lower incidence of cGvHD relative to all but fully matched sibling transplants, GvHD remains a major cause of morbidity and mortality post UCBT.…”
mentioning
confidence: 99%
“…However, theoretically, this process could be simply combined with one of the two ex vivo expansion methods described above and this may result in even more rapid engraftment. Cutler et al 44 used an alternative strategy involving the brief ex vivo incubation of one of two CB units with dimethyl prostaglandin E2. Dimethyl prostaglandin E2 has pleotropic effects on HPCs, upregulating genes involved in stem cell homing, proliferation and survival.…”
mentioning
confidence: 99%
“…PGE2-treated primate CD34 + mPB stem cells exhibit stable multilineage repopulation [194]. A phase I clinical trial with 16,16-dimethyl prostaglandin E2-treated cord blood demonstrated safety and accelerated neutrophil recovery in patients receiving this treatment compared to controls [195].…”
Section: Prostaglandin E2 (Pge2)mentioning
confidence: 99%
“…No adverse effects were observed with the infusion of NiCord. NiCord engraftment remained stable in patients, and the patients who received the NAM-treated culture achieved earlier median neutrophil [190] AhR antagonist (SR1) phase I/II trial enhances neutrophil recovery antagonizing an acryl hydrocarbon receptor [191][192][193] PGE2 2 h phase I trial enhances neutrophil recovery enhancing homing, survival, and proliferation of HSCs [65,194,195] TPO receptor agonist (NR-101) 7 d repopulation 2.9-fold activating STAT5 and Hif-1alpha [197] UM171 12 d repopulation 13-fold inhibiting erythroid and megakaryocytic differentiation [192] recovery than those given untreated cord blood [190]. EX-527, another SIRT1 inhibitor, also inhibits differentiation of human CD34 + cells [189].…”
Section: Sirtuin 1 (Sirt1) Inhibitormentioning
confidence: 99%